Intellectual capital for developing new human resources in business organizations: an analytical study in the General Directorate of Human Resources - Qais Abdul Hadi Saleh (Iraqi Journal for Administrative Sciences, 2025)
In the framework of this research we have tried to review the available literature on the concept of administrative intellectual capital and demonstrate the importance of the fact that the intellectual capital represents one of the competitive advantages of contemporary organizations. Notes the transition from a focus on organizations competitive units provide goods and services in a competitive framework based on the achievement of excellence qualitative and creativity and innovation continuously to regard these organizations systems of knowledge are trying to create a competitive advantage based on the capabilities of non-concrete and new, which is uncharacteristic in previous periods. The researcher adopted a model was built by default after a review of the literature relevant to the subject under President hypothesis and origin of the sub-set of assumptions. As well as the use of a set of statistical methods in data analysis based on the five-Likert scale in the design of the questionnaire and the coefficient of correlation to determine the relationship between the variables of the study results were obtained using statistical software (SPSS, V.18). The study provided a set of conclusions and recommendations that are consistent with the results of the analysis and the most important of these conclusions was: It became clear that there is a strong correlation between the relationship (intellectual capital and human resource development) and indicate this relationship on the Organization's interest in the study population to these principles that contribute to cognitive superiority over the rest of the competition organizations. While the study made a recommendation the need for human resource development through investment and the development of intellectual capital and private organizations in seeking to achieve a competitive edge over the rest of the organizations.